PENGARUH SHOLAT TAHAJUD TERHADAP TINGKAT KEDISIPLINAN SANTRI PUTRA - Muhamad Risky Ramdani Putra; Mujiburrohman Mujiburrohman; Mu'in Abdulah (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
The thing that must always be considered by the santri is the discipline of the rules that have been set. One example is the discipline of the santri in terms of waking up, the santri are required to wake up from their sleep at 3.30 WIB after that they perform the midnight prayer and continue with the dawn prayer in congregation right on time. However, not all students can wake up from their sleep on time so that it is the cause of being late to attend the congregational morning prayers at the mosque. So from this problem, the author wants to make observations on the implementation of the midnight prayer for students and also conduct pretest and posttest experiments on students who are used to waking up after the dawn call to prayer by getting them to be able to wake up from their sleep at 3.30 WIB and continue with the midnight prayer and also morning prayers in congregation. The purpose of this research was to improve the discipline of students through midnight prayer therapy every night. The method used was true experimental quantitative (one group pretest and posttest design. The results obtained showed that there was an effect of midnight prayer on the discipline level of students. This research can be concluded in Data processing was in the form of: paired sample t-test as the latest test to obtain data in the form of Sig.2 0.00 <0.05 which indicates the effect of midnight prayer therapy on the discipline level of students.